ответ: 1целая 1/3; 1/4
Пошаговое объяснение:
1.
3целых 1/6 - (х + 1целая 1/12) = 1/4
3целых 1/6 - х - 1целая 1/12 = 1/4
3целых 2/12 - 1целая 1/12 - х = 3/12
2целых 1/12 - х = 3/12
х = 2целых 1/12 - 3/12
х = 1целая 13/12 - 3/12
х = 1целая 10/12
х = 1целая 2/6
х = 1целая 1/3
2.
3целых 5/36 - (1целая 4/9 - х) = 1целая 17/18
3целых 5/36 - 1целая 16/36 + х = 1целая 34/36
х = 1целая 34/36 + 1целая 16/36 - 3целых 5/36
х = 3целых 14/36 - 3целых 5/36
х = 9/36
х = 1/4
ответ: 1целая 1/3; 1/4
Пошаговое объяснение:
1.
3целых 1/6 - (х + 1целая 1/12) = 1/4
3целых 1/6 - х - 1целая 1/12 = 1/4
3целых 2/12 - 1целая 1/12 - х = 3/12
2целых 1/12 - х = 3/12
х = 2целых 1/12 - 3/12
х = 1целая 13/12 - 3/12
х = 1целая 10/12
х = 1целая 2/6
х = 1целая 1/3
2.
3целых 5/36 - (1целая 4/9 - х) = 1целая 17/18
3целых 5/36 - 1целая 16/36 + х = 1целая 34/36
х = 1целая 34/36 + 1целая 16/36 - 3целых 5/36
х = 3целых 14/36 - 3целых 5/36
х = 9/36
х = 1/4